Mathematics in the Subject of Vegetable Processing Production - Ai Tusi fatimah; Sri Solihah (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2020)
Mathematics studied in SMK should have relevance with student competencies to support vocational school education goals. This study aims to explore the role of mathematics in the Vegetable Processing Production Subject. This subject is studied by students of the Agricultural Product Processing Agribusiness Competency Vocational School. This research uses a qualitative approach. The role of mathematics in the production of vegetable processing is explored from the perspective of productive teachers and documents. The analysis to explore the role of mathematics and its relevance to mathematics content and mathematics learning. The results show that the role of mathematics is to calculate and measure the various needs for tools, materials, and business planning analysis for the production of vegetable processing. The role of mathematics has relevance to the mathematical content of numbers and measurements. The integration of vegetable product processing production contexts can be done to construct a mathematical concept or present a mathematical task situation as an effort to develop mathematical understanding by student expertise.